Evaluation of Hepatotoxicity Effects on Fruits and Vegetables: Evaluation of the protective activity of methanolic extracts from exotic fruits and vegetables against hepatotoxicity (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Liver toxicity in world health problems is a major challenge. Food and Drug Administration (FDA), which causes induced hepatotoxicity, is withdrawing many of the drugs from the market. In this study, in vitro hepatotoxicity, enhancing activity of methanoic extracts from different parts (peel, pulp and seed) of carbon-tetrachloride exotic fruits and vegetables (CCl4) was studied. For lipid peroxidation (LPO), a free radical scavenging and sodium dismutase (SOD) test, chicken liver cell suspension treated with CCl4 was employed. Different extracts from exotic fruits and common vegetables have shown a powerful antioxidant effect. Methanoic extract from some unused parts of vegetables and fruits (peel and seed) even showed hepatoprotective action but the remarkable hepatoprotective action was shown among all these fibergine pulp (vegetables) and passion fruit pulp (exotic fruit) Thus we conclude that there was notable protective activity in CCl4 induced by the methanoic extracts of exotic fruits and vegetables.